2008
DOI: 10.1007/s11145-008-9152-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between sixth-graders’ reading comprehension and two different measures of print exposure

Abstract: This study examined sixth-graders' reading comprehension and component reading abilities in relation to two measures of print exposure: an author recognition test (ART) involving fiction authors and a reading habits questionnaire (RHQ) about children's voluntary reading for enjoyment across various genres. The ART correlated only with children's fiction book reading habits, not with other habits such as nonfiction book or magazine reading, and had a stronger relationship to all tested reading abilities than di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 29 publications
5
45
0
5
Order By: Relevance
“…Therefore, it is not the case that past print exposure predicts reading skills but rather exposure to extended texts, in particular fiction book reading. These results are consistent with research demonstrating a closer relationship between reading skills and book reading compared to other text types (Anderson et al, 1988) and fiction book reading in particular (Spear-Swerling et al, 2010). However, the association between reading skill and reading activities is reciprocal (Mol & Bus, 2011), as students' reading habits are also influenced by their reading skills.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, it is not the case that past print exposure predicts reading skills but rather exposure to extended texts, in particular fiction book reading. These results are consistent with research demonstrating a closer relationship between reading skills and book reading compared to other text types (Anderson et al, 1988) and fiction book reading in particular (Spear-Swerling et al, 2010). However, the association between reading skill and reading activities is reciprocal (Mol & Bus, 2011), as students' reading habits are also influenced by their reading skills.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Anderson et al (1988) found that time spent reading books was more strongly associated with reading comprehension and reading speed than other text types (e.g., comics, newspapers and magazines). Similarly, Spear-Swerling, Brucker and Alfano (2010) found that fiction book reading was more closely associated with various reading-related skills (i.e., word reading, oral comprehension, vocabulary and reading comprehension) compared to other reading habits.…”
Section: Reading Frequency and Reading Habitsmentioning
confidence: 87%
See 2 more Smart Citations
“…Likewise, Kantarcı (2015), in his study on the 4th grade students, revealed that reading motivation explains 9% of academic achievement of Turkish course and that reading motivation is more effective than other variables in increasing academic achievement in this subject. Reading motivation influences reading frequency, vocabulary knowledge, vocabulary, reading fluency and reading comprehension (McGeown, Duncan, Griffiths and Stothard, 2015;Spear-Swerling, Brucker and Alfano, 2010) as well as academic achievement and it brings the significance of its effect on reading attitude into the forefront. The positive relationship between reading attitude and reading comprehension (Sallabaş, 2008;Şeflek Kovacıoğlu, 2006), academic achievement of Turkish course (Kocaarslan, 2016;Baş and Şahin, 2012;Karabay and Kuşdemir Kayıran, 2010) and overall academic achievement (Crosby, 2013;Ward, 2013;Kaniuka, 2010;Martinez, Aricak and Jewell, 2008) clearly demonstrates the impact of this affective variable on reading skills and academic life.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%